LARGE ARTERY HEMODYNAMICS IN HEALTHY YOUNG PEOPLE - G. G. Efremushkin; E. A. Denisova; T. V. Filippova (Российский кардиологический журнал)
In total, 22 healthy people (20 men, 2 women), aged 19–46 years (mean age 32,2±1,2 years), were examined. Mean blood pressure (BP) was 118,4±1,4/177,3±1,4 mm Hg. Repeated large artery Doppler ultrasound was performed. In healthy people, maximal and minimal blood flow velocity in common carotid artery was 1,5 and 2,8 times higher than in femoral and brachial arteries, respectively (р<0,001). Volume and energy components of blood flow are maximal in large arteries, due to greater vessel diameter and blood flow velocity. Pulse wave velocity increases with increasing distance from the heart and does not depend on blood flow parameters. The additional wave, following the pulse wave, is formed due to aorta damping qualities. Compression and nitroglycerin tests in health people demonstrate uniform results: increased intima-media thickness and increased artery diameter.